(untitled) (Revista científica Olimpia, 2019)
This research addresses a problem related to the conception of learning tasks in the subject of criminology and particularly referred to the development of motivation for learning in law students. Studies carried out during the course 2017-2018 showed difficulties that students presented in the use of pre-professional content and resources to perform in their social-work context, as well as inadequacies in the didactic conception of learning tasks when not taking into account the unity of the affective and the cognitive, or link with practice. Consequently, the objective of this research is to study the theoretical foundations that support a system of contextualized tasks that favor the motivation for learning in the subject of criminology for law students, using different methods and techniques at the theoretical and empirical level.